AKI in Multiple Myeloma: Paraproteins, Metabolic Disturbances, and Drug Toxicity. Issue 3 (November 2017) - Shah, Mamta; Perazella, Mark A.
Acute kidney injury (AKI) is a frequent complication of multiple myeloma and is due predominantly to paraprotein-mediated nephrotoxicity. AKI occurs in myeloma patients due to a number of causes, including prerenal azotemia, metabolic nephrotoxicity from hypercalcemia and tumor lysis syndrome, proximal tubular injury, cast nephropathy, and drug-related nephrotoxicity. Importantly, AKI may develop in patients with known multiple myeloma or as an initial manifestation of this monoclonal disease. Diagnostic work-up includes the demonstration of monoclonal proteins, the search for the underlying B-cell clone, and a kidney biopsy, in many instances. Myeloma management involves treatment with chemotherapeutic agents to rapidly lower light chain levels, along with supportive measures that optimize volume status, correct metabolic disturbances, reduce proteinuria, and minimize nephrotoxin exposure. Extracorporeal therapies, such as plasma exchange and high-cutoff hemodialysis, have been employed, but their utility remain uncertain. The presence of AKI in myeloma patients appears to be associated with a higher mortality. Partial and full renal recovery are associated with better survival.